Continuing the Legacy at Nordic Lodge: Succession Planning at an Iconic Family-Owned Restaurant. (July 2019) - Graham, Emily; Mischel, Leann
The Nordic Lodge is an iconic family-owned restaurant located in Charlestown, Rhode Island. The restaurant is equally owned by third-generation siblings Nancy Log, Lisa Brown, and Steve Persson. Steve's wife, Lorna, also helps to manage the restaurant. It is established as a private corporation with both voting and nonvoting stock. The current generation is not ready to retire but recognizes the need to set up a succession plan. They realize that a good plan will take several years to put in place and want to ensure that the legacy of the restaurant continues. There are presently eight children in the fourth generation, all of whom have expressed an interest in being a part of the business. Having reached a crossroad in their development, the family is unsure how to proceed with succession planning. They are looking for advice on how to move forward to ensure that all children have the opportunity to work in the restaurant and that future decisions are equitable. The family would also like to determine how shares should be passed down .